Production of capsules of oil palm pollen. (2021)
Prototype capsules of the pollen grains of the oil palm were produced with a view to their being used as a food supplement. Oil palm pollen was chosen because the tree is indigenous and popular, with numerous socio-economic uses including in local cuisine as palm oil and palm kernel oil. Proximate chemical and mineral analyses of the pollen showed its appreciable nutritive value as a supplement for Vitamin A and iron in particular. Vitamin A performs very important functions in the human body, especially regarding vision, reproduction, immunity, and the normal functioning of several major organs. The optimal utilization of vitamin A by the human body is enhanced by the inclusion of fat, protein, iron, and zinc in the diet; the occurrence of these nutrients in oil palm pollen reinforces its value as a Vitamin A supplement. Non-toxicity of the capsules in laboratory animals requires clinical validation for humans.